POLISEMI LEKSEM (上 Shàng) PADA SERIAL DRAMA《我的父亲母亲》Wǒ de fùqīn mǔqīn - Noni, Nur Nasharuddin; Fatoni, Ahmad Sirfi; Ernawati, Ernawati (Universitas Negeri Makassar, 2024)
Elements in language such as phrases, words, and sentences can be analyzed using linguisticstudies, including semantic studies related to language meaning. This article discusses thepolysemy of lexemes 上 (shàng) in the drama series 我的父亲母亲 (Wǒ de fùqīn mǔqīn).This paper uses a qualitative approach, using note-takingand listening and translationtechniques. Data was collected from Mandarin drama series sources and analyzed withreference to representative sources. 22 data were found and 14 data were described. Theresearch results show that there are many dialogues containing the lexeme 上(shàng),indicating that this word is often used in Mandarin both in writing and conversation. In wordformation analysis, the lexeme 上 (shàng) is a free morpheme that can form new words andmeanings. The findings show that the diversity of meanings is still related to basic meaningsand new meanings which must be seen from various aspects in forming meaning.Key words: lexeme 上 (shàng), meaning, polysemy